Assessment of safety in the Bering Sea/Aleutian Island crab fleet - Lucas, Devin; Case, Samantha; Teske, Theodore; De Leon, Alexis; Kloczko, Dimitreus; National Institute for Occupational Safety and Health.
This report provides a detailed analysis of work-related injuries and vessel safety issues within the Bering Sea/Aleutian Island (BSAI) crab fleet to identify both hazards and opportunities for safety improvements within the fleet. The BSAI crab fleet is comprised of vessels averaging 90-120 feet in length that use pot gear to harvest crab, and either process the catch on board or deliver it to on-shore or floating processors (Woodley & Medlicott, 2001). The fishing seasons for various species of BSAI crab begin in October and typically end by May. The findings and recommendations in this report are especially relevant to the North Pacific Fishery Management Council, United States Coast Guard, and the Bering Sea/Aleutian Island crab fleet. The BSAI crab fleet was identified as the most hazardous commercial fishery in the United States during the 1990s (Lincoln et al., 2013). During that decade, 73 crewmembers in the fleet died as a result of vessel disasters, falls overboard, or on-board injuries (Lincoln et al., 2013). Although safety regulations in place at that time required vessels to carry lifesaving equipment, such as immersion suits and life rafts, the regulations did not address the problem of overloading vessels with crab pots, a major cause of vessel disasters and deaths. This gap in safety regulations was partially corrected by the Coast Guard in 1999 with the introduction of the "At-the-Dock Stability and Safety Compliance Check" program, in which Coast Guard personnel checked crab vessels in Dutch Harbor prior to departure to ensure that each was loaded in compliance with their stability instructions. Subsequent to the introduction of this program, along with other possible factors such as changes in safety culture, the number and rate of fatalities in the fleet decreased during the period 1999-2012 (Lincoln et al., 2013; Woodley et al., 2009). In addition to the Coast Guard Compliance Checks, the BSAI crab fishery changed in 2005 from a derby-style race for fish to a quota-based (rationalized) ...